1999
DOI: 10.1038/sj.jhh.1000808
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of ambulatory blood pressure monitoring in daily practice

Abstract: The reproducibility of ambulatory blood pressure monitoring (ABPM) was investigated in 45 untreated hypertensive patients in an out-patient clinic. Subjects with symptoms or diseases which could probably give rise to an increase in blood pressure (BP) variability were excluded. Patients underwent office BP (OBP) measurements and ABPM measurements with the Oxford Medilog device twice. The data were edited following previous set standards. Reproducibility of ABPM was good for the group: 24 h ABPM difference 0/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 25 publications
2
25
2
Order By: Relevance
“…Previously, similar data have been reported in healthy normotensive adults as well as in untreated and treated patients with arterial hypertension [32,[35][36][37][38][39][40][41][42]. In accordance with our results, many studies have shown that ambulatory BP values are more reproducible than office BP values [13,[43][44][45][46].…”
Section: Discussionsupporting
confidence: 81%
“…Previously, similar data have been reported in healthy normotensive adults as well as in untreated and treated patients with arterial hypertension [32,[35][36][37][38][39][40][41][42]. In accordance with our results, many studies have shown that ambulatory BP values are more reproducible than office BP values [13,[43][44][45][46].…”
Section: Discussionsupporting
confidence: 81%
“…Although this could mean that antihypertensive treatment based on SBPM leads to worse BP control as compared with OBPM-based treatment, we must realize that the reproducibility of ABPM is limited. 30 Although differences in mean ABPM and OBPM values between both groups are small and perhaps not relevant for a patient as an individual, these results cannot be ignored, because even small differences can have serious consequences with respect to cardiovascular complications in the population at large. Indeed, a meta-analysis of individual data for 1 million adults in 61 prospective studies showed that a 2-mm Hg-lower systolic BP value would eventually lead to a 10% lower stroke mortality and Ϸ7% lower mortality from ischemic heart diseases or other vascular causes in middleage patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies specifically directed to reproducibility of the presentation of blood pressure drop during sleep showed no statistical differences after 4 examinations of ambulatory blood pressure monitoring in the same patient, performed on the same weekday at 30-day intervals 36 . The possible factors involved in the reproducibility of ambulatory blood pressure monitoring could be the following: different daily activities on different days of examination, a reduction in accuracy due to very high levels of blood pressure, differences in the quality of sleep, and limitation of the examination in conditions of ambulatory measurements 37 . Noninclusion of patients with diagnosed or suspected secondary hypertension according to medical requisitions aimed to exclude patients with previous alterations in blood pressure drop during sleep, which do not depend on the quality of sleep 23 .…”
Section: Discussionmentioning
confidence: 99%